Cardiolipin occupancy profiles of YidC paralogs reveal the significance of respective TM2 helix residues in determining paralog-specific phenotypes - Mishra, Surabhi; van Aalst, Evan J.; Wylie, Benjamin J.; Brady, L. Jeannine (Frontiers in Molecular Biosciences, 2023)
YidC belongs to an evolutionarily conserved family of insertases, YidC/Oxa1/Alb3, in bacteria, mitochondria, and chloroplasts, respectively. Unlike Gram-negative bacteria, Gram-positives including Streptococcus mutans harbor two paralogs of YidC. The mechanism for paralog-specific phenotypes of bacterial YidC1 versus YidC2 has been partially attributed to the differences in their cytoplasmic domains. However, we previously identified a W138R gain-of-function mutation in the YidC1 transmembrane (TM) helix 2. YidC1 W138R mostly phenocopied YidC2, yet the mechanism remained unknown. Primary sequence comparison of streptococcal YidCs led us to identify and mutate the YidC1 W138 analog, YidC2 S152 to W/A, which resulted in a loss of YidC2and acquisition of YidC1-like phenotype.The predicted lipid-facing side chains ofus to propose a role for membrane phospholipids in specific-residue dependent phenotypes of S. mutans YidC paralogs. Cardiolipin (CL), a prevalent phospholipid in the S. mutans cytoplasmic membrane during acid stress, is encoded by a single gene, cls. We show a concerted mechanism for CL and YidC2 under acid stress based on similarly increased promoter activities and similar elimination phenotypes. Using Coarse Grain Molecular Dynamics simulations with the Martini2.2 Forcefield, YidC1 and YidC2 wild-type and mutant interactions with CL were assessed in silico. We observed substantially increased CL interaction in dimeric versus monomeric proteins, and variable CL occupancy in YidC1 and YidC2 mutant constructs that mimicked characteristics of the other wild-type paralog. Hence, paralog-specific amino acid-CL interactions contribute to YidC1 and YidC2-associated phenotypes that can be exchanged by point mutation at positions 138 or 152, respectively.